1989
DOI: 10.1021/om00109a014
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotelluration of acetylenes: synthesis of vinylic tellurides, divinyl tellurides, and 1-(organyltelluro)-1,3-butadienes

Abstract: Organyltellurols generated in situ by NaBH4 reduction of diorganyl ditellurides react with acetylenes in refluxing ethanol to give vinylic tellurides of Z configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 5 publications
(7 reference statements)
0
31
0
Order By: Relevance
“…Bis-vinylic tellurides can be prepared by reacting monosubstituted alkynes with a hydrotellurating system prepared from elemental tellurium and sodium borohydride in a mixture of ethanol / aqueous sodium hydroxide 15 . The stereochemistry of the resulting vinylic tellurides is also Z (Equation 2).…”
Section: Hydrotelluration Of Alkynesmentioning
confidence: 99%
“…Bis-vinylic tellurides can be prepared by reacting monosubstituted alkynes with a hydrotellurating system prepared from elemental tellurium and sodium borohydride in a mixture of ethanol / aqueous sodium hydroxide 15 . The stereochemistry of the resulting vinylic tellurides is also Z (Equation 2).…”
Section: Hydrotelluration Of Alkynesmentioning
confidence: 99%
“…Isolated terminal alkyne 34 (Table 1, Entry 10), however, suffered loss of regioselectivity yielding 1,2-and 2,2-disubstituted vinylic tellurides 44 and 45, in favour of the 1,2-disubstituted vinylic telluride 44, as previously documented for isolated alkynes. 21,24,25 Unfortunately, in our case, an inseparable mixture was obtained. Efficient methodology to circumvent this problem, however, has been reported to regioselectively give the 1,2-disubstituted cis-vinylic tellurides by hydroboration or hydrometallation of 1-alkynyltellurides.…”
Section: Resultsmentioning
confidence: 58%
“…A variety of alkynes (i.e., 1) ( Table 1, [25][26][27][28][29][30][31][32][33][34] were treated with dibutyl ditelluride 2 and sodium borohydride under standard conditions 21,22 to give cis-vinyltellurides (i.e., 3) in 58-94% yield (Table 1, 35-43) (Scheme 1). For all conjugated alkynes, the cis-vinyltellurides were obtained with excellent regio-and stereo-selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38,[61][62][63][64] Analysis of the 1 H NMR and 13 C NMR spectra showed that all alkene compounds presented data in full agreement with their assigned structures. The stereochemistry of the obtained alkenes was easily established.…”
Section: Resultsmentioning
confidence: 97%